Development to the blastocyst stage, the oxidative state, and the quality of early developmental stage of porcine embryos cultured in alteration of glucose concentrations in vitro under different oxygen tensions - Ohnuma Katsuhiko; Somfai Tamás; Ozawa Manabu; Fahrudin Mokhamad; Kikuchi Kazuhiro; Karja Ni; Noguchi Junko; Kaneko Hiroyuki; Nagai Takashi (BMC, 2006)
Abstract Background Recent work has shown that glucose may induce cell injury through the action of free radicals generated by autooxidation or through hypoxanthine phosphoribosyltransferase inhibition. The effect of glucose during early in vitro culture (IVC) period of porcine embryos on their developmental competence, contents of reactive oxygen species (ROS) and glutathione (GSH), and the quality of the blastocysts yielded was examined. Methods In vitro matured and fertilized porcine oocytes were cultured for the first 2 days (Day 0 = day of fertilization) of IVC in NCSU-37 added with 1.5 to 20 mM glucose (Gluc-1.5 to -20 groups) or pyruvate and lactate (Pyr-Lac group). The embryos in all groups were cultured subsequently until Day 6 in NCSU-37 with 5.5 mM added glucose. The ROS and GSH level were measured at Day 1 and 2. DNA-fragmented nuclei and the total cell numbers in blastocyst were evaluated by TUNEL-staining at Day 6. Results Under 5% oxygen the blastocyst rates and total cell numbers in the blastocysts in all glucose groups were significantly lower than that in the Pyr-Lac group. Similar result in blastocyst rate was found under 20% oxygen (excluding the Gluc-10 group), but total cell numbers in the blastocysts was similar among the groups. At both oxygen tensions, the H2O2 levels of Day 1 embryos in all glucose groups were significantly higher than that in the Pyr-Lac group, while only the Gluc-1.5 group of Day 2 embryos showed a significantly higher H2O2 level than that in the Pyr-Lac group. The GSH contents of either Day 1 or Day 2 embryos developed under 5% oxygen were similar among the groups. Only the content of Day 2 embryos in 1.5 mM group was significantly lower than the embryos in the Pyr-Lac group under 20% oxygen. Total cell numbers in the blastocysts (except in the Gluc-20 group) were significantly lower in the embryos cultured under 20% oxygen than 5% oxygen. Only the Gluc-20 blastocysts developed under 5% oxygen showed significantly higher DNA fragmentation rate than those of Pyr-Lac blastocysts. Conclusion These results show that a decrease in developmental ability of embryos cultured by use of glucose instead of pyruvate and lactate after the ferilization may be due to the rise in ROS generation in Day 1 embryos. Moreover, results from this study suggest that the concentration of glucose in the medium that can be used by the Day 1-2 embryos is limited to 3.5 mM and exposure to higher glucose concentrations does not improve embryo development.